Polyethersulfone/HFO mixed matrix membrane for enhanced oily wastewater rejection - Ikhsan, S. N. W.; Abdullah, N.; Yusof, N.; Aziz, F.; Misdan, N.; Hairom, Nur Hanis Hayati (Penerbit Universiti Teknologi Malaysia Press, 2017)
The recent growth of oil and gas industry has led to the increase of oily wastewater release. Membrane technology has been in the spotlight in recent advancement to treat the oily wastewater. Fouling due to surfactant adsorption and/or oil droplets plugging the pore has become one of the major hindrances in most of the research on oily wastewater treatment. In this work, self-synthesized hydrous ferric dioxide nanoparticles (HFO NPs) via chemical precipitation method were incorporated in polyethersulfone (PES) to fabricate a novel nanocomposite mixed matrix membranes (MMMs) for ultrafiltration (UF). The morphologies and physicochemical properties of prepared HFO NPs and MMMs were characterized using Scanning Electron Microscopy (SEM) and Transmission electron microscope (TEM), contact angle goniometer, before further subjected to water permeation test and oil rejection test. It was found that contact angle of membrane decreased remarkably with an increase in HFO nanoparticle loading from 70° to 38° at which proved its improved hydrophilicity which led to a significant rise in permeate flux, achieving 168.06 L/m2h bar in comparison to 63.67 L/m2h bar shown by the plain PES membrane. Total rejection of oil (100% rejection) demonstrated by the MMMs has confirmed the superior potential of PES/HFO UF membrane for total purification of oily wastewater especially to be reused in oilfield and refinery processes as well as to be released to the environment.